PERKEMBANGAN ETIKET BATIK DI KAUMAN SURAKARTA TAHUN 1950-1970 - Hermansyah Muttaqin (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2011)
Research based on "The Dynamic of Etiket Batik in Kauman Surakarta During 1950–1970" is done to answer a problem that based to three main questions; the reason of appearance of batik etiket in Kauman Surakarta, and how the dynamic of etiket batik is created by batik industrialist in Kauman Surakarta during 1950-1970. The aim of this research is to trace they appearance the use of batik etiket in Kauman Surakarta and the existence up the 1970's, to know the variety of etiket batik dynamic made by batik industrialist in Kauman Surakarta during 1950-1970. The appear of using batik etiket started from the appear of batik industry in Kauman Surakarta. The increase of kain batik tulis needed cause the wife of abdi dalem pamethakan in Kauman doing the double jobs as creater and batik tulis trader, that start the batik industrialist in Kauman. The chance from batik home industry to industry happen when the batik cap technology appear. In the marketing of batik cap-capan use etiket as trade mark identity. The dynamic of batik etiket in Kauman can be followed from the phonetic of the etiket, so can be classified in to two periods etiket made.Keywords: Dynamic, label, Kauman Surakarta